Kontekstualisasi Hadis tentang Jihad dan Relevansinya dalam Konflik Timur Tengah - Firmanda Taufiq; Ayu Maulida Alkholid (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Contextualization of Hadith about Jihad and Its Relevance in the Middle East ConflictThis article’s aimed to study and trace the traditions related to jihad in the phenomenon of conflict in the Middle East. This shows that basically the understanding of the hadith is something important to know how the context of the hadith on the phenomena that occur. This is because, if we look at the events of the conflict that took place in the Middle East, that the combatants and terrorists involved in the conflict in the region are based on the concept of jihad. This situation indicates a perspective on the relationship between understanding jihad and the occurrence of conflict. They think that what they have actually done is jihad. Meanwhile, it is wrong and has tarnished the understanding on the basis of the jihad. Therefore, this study discusses the contextualization of the hadith on the concept of jihad and its relevance in the conflicts that occurred in the Middle East. This research uses descriptive analysis method on the hadiths about jihad. Through this research, it was found that the conceptions of jihad in the hadiths were misunderstood by combatants and terrorists, basically what they interpreted as jihadist traditions.